Seroprevalence of hepatitis B virus surface antigen among pregnant females attending antenatal clinic at a tertiary care hospital in North India - Jahan, Noor; Kumar, Anil; Nigar, Asma; Ahmad, Siraj; Khatoon, Razia; Chaudhary, Nitin (International Journal of Research in Medical Sciences, 2019)
Background: Hepatitis B infection is one of the most common public health problems worldwide. Hepatitis B virus Surface Antigen (HBsAg) positive mothers may transmit the virus vertically to neonates transplacentally during pregnancy, perinatally during delivery or postnatally through breast milk. Such neonates being carriers of virus are at a very high risk of developing chronic liver diseases at a younger age and also, they act as reservoirs of infection in the community. Objective of the study is to evaluate the seroprevalence of HBsAg in pregnant females attending Antenatal Clinic. Methods: A hospital based cross-sectional study was done from January to June 2019. A total of 840 pregnant females were included in the study who attended Antenatal Clinic for routine checkup whose blood samples were sent to Microbiology Laboratory for screening of HBsAg by Enzyme Linked Immunosorbent Assay (ELISA). Results: Out of 840 pregnant females included in the study, 8 were reactive to HBsAg, hence, prevalence was found to be 0.95%. The seroprevalence of HBsAg was found to be more (1.40%) in 26-35 year females. Maximum seropositivity was seen in females from urban areas (1.0%), those attending OPD of ANC (1.03%) and those who belonged to lower socio-economic class (1.02%). Conclusions: Routine free screening for HBV infection should be offered to all antenatal females to reduce the risk of vertical transmission to the neonates born to infected mothers, thereby, preventing them from becoming carriers and developing chronic hepatitis and hepatocellular carcinoma later in life.